Evaluación del mercado turístico proyectándose hacia un turismo accesible en el destino Manta/Manabí - Velásquez Cedeño, Zaira Fernanda (2019)
This research was aimed to evaluate the tourism market in the destination of Manta / Manabí due to its projection towards accessible tourism, which is based on a descriptive methodology, of a non-experimental nature. The first stage embodied the review of literature related to accessibility in tourist destinations, to establish the methodology of this work, the criteria were analyzed by the comparison of five authors, who were: Damazio and Gallardo (2009), Foundation ONCE (2009), Guajardo , García and Sánchez (2012), Martos (2012), Medina (2017), this process based on quantitative and qualitative work, relies on the design and application of surveys, interviews, data sheets, SWOT matrix; and in addition to collecting information from secondary sources for analysis. The results of the research bring about important information on international documents regarding the validation of the rights of people with disabilities, as well as the current laws and regulations of the Ecuadorian state with respect to universal criteria, tourism and the inclusion of people with disabilities, as well as the perception of domestic tourism demand in terms of accessibility, the current reality of various elements of the tourism supply, actions carried out by public and business actors oriented to planning, accessibility management at the destination; so that the data collected establish the most obvious problems regarding accessibility in tourism of the study object, which were aimed at establishing immediate strategies and actions on key issues for the projection of accessible tourism in the destination of Manta.